2013
DOI: 10.3386/w19234
|View full text |Cite
|
Sign up to set email alerts
|

Health and Health Behaviors during the Worst of Times

Abstract: Previously circulated as "Health and Health Behaviors during the Worst of Times: Evidence from the Great Recession." Erdal Tekin gratefully acknowledges support from the Gary and Stacey Jacobs Fellowship. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 25 publications
4
62
3
1
Order By: Relevance
“…Despite this, average levels of wellbeing and self-reported health do not appear to have declined. These findings provide support to some recent papers which have reported similar findings for the US (Tekin et al (2013) and Ruhm (2013)) and for Ireland (Walsh, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite this, average levels of wellbeing and self-reported health do not appear to have declined. These findings provide support to some recent papers which have reported similar findings for the US (Tekin et al (2013) and Ruhm (2013)) and for Ireland (Walsh, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…However, the emerging evidence is that the relationship between macro-economic events and health is loosening e.g. Tekin et al (2013) and Ruhm (2013). Deaton (2012) also found a very weak relationship between subjective wellbeing and the recession in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…For the category "$75,000 or more," I assigned an annual income of $112,500 (150% of $75,000). The previous studies that used the BRFSS adopted the same method Tekin et al, 2013). 16 Smoking is included because there is evidence that individuals who quit smoking typically gain weight, and an increase in the price of cigarettes has contributed to a rise in obesity (Chou et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…7 Tekin et al (2013) showed that most measures of health status were not significantly influenced by the unemployment rate. However, smoking and drinking declined, and exercise rose during the Great Recession.…”
Section: Prior Literaturementioning
confidence: 99%
“…Tekin et al (2013) With regard to a sharp fall in value of wealth, Cotti et al (2015) reveals that stock market crashes are related to declines in self-reported mental health and risky health behaviors such as more smoking and drinking. Fiuzat et al (2010) show that there is a significant correlation between periods of stock market crashes and growth in acute myocardial infarction (AMI) rates.…”
Section: Prior Literaturementioning
confidence: 99%